The Cambridge dictionary of philosophy (Cambridge Univ. Press, 1995)
Features essays about major and minor philosophers; surveys all the subdisciplines of philosophy, such as ethics, religion, epistemology, and logic; and includes brief definitions of philosophically important terms. Arranged alphabetically with cross-references.